Proteins and signaling pathways response to Wenjingtongluo drug-contained serum in IHUVECs: an explorative proteomic study: Response to Wenjingtongluo DS in IHUVECs - Xu, Weimin; Qian, Jiajia; Xu, Qi; Cai, Ren; Yang, Guo; Wei, Jiarong; Huang, Guicheng (Cellular and Molecular Biology, 2023)
Angiogenesis is a dynamic and complex process leading to the development of new vessels from pre-existing vessels, which played a major role in pathological processes in many diseases. The present study aimed to investigate the effect of drug-contained serum of Traditional Chinese medicine (TCM) Wenjingtongluo decoction (WJLTD) on antiangiogenesis in Immortalized Human Umbilical Vascular Endothelial cells (IHUVECs), and elucidate the possible mechanisms based on proteomic analysis. Cells were treated with the drug-contained serum of the Drug-contained Serum (DS) of WJLTD and the blank serum (BS). The antiangiogenesis capacity of DS was evaluated using wound healing assay, Transwell, and tube formation assay. We performed three biological replicates to compare large-scale differential protein expression between two groups by tandem mass tag (TMT) labeling technology based on liquid chromatography-mass spectrometry analysis (LC-MS/MS). Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed for the general characterization of overall enriched proteins. For validation of the results of TMT, the candidate proteins were verified by parallel reaction monitoring (PRM) analysis. The results showed that 4% DS could inhibit the migration process of IHUVECs according to wound healing assay and Transwell. And tube formation ability was also dramatically inhibited (p<0.001). TMT analysis revealed 148 differentially expressed proteins between two groups that were identified and quantified. The further validation results of the two candidate proteins, Ferritin heavy chain (FTH1) and Ferritin light chain (FTL) from the Ferroptosis pathway, which played an important role in DS treatment, were consistent with those of LC-MS/MS. In conclusion, this is the first proteomics-based study to report the mechanism underlying DS treatment for angiogenesis. Further functional verification of the potential signaling pathways and the enriched proteins is warranted.